A Reduction in Age-Enhanced Gluconeogenesis Extends Lifespan - Hachinohe, Mayumi (Public Library of Science, 2013)
The regulation of energy metabolism, such as calorie restriction (CR), is a major determinant of cellular longevity. Although augmented gluconeogenesis is known to occur in aged yeast cells, the role of enhanced gluconeogenesis in aged cells remains undefined. Here, we show that age-enhanced gluconeogenesis is suppressed by the deletion of the tdh2 gene, which encodes glyceraldehyde-3-phosphate dehydrogenase (GAPDH), a protein that is involved in both glycolysis and gluconeogenesis in yeast cells. The deletion of TDH2 restores the chronological lifespan of cells with deletions of both the HST3 and HST4 genes, which encode yeast sirtuins, and represses the activation of gluconeogenesis. Furthermore, the tdh2 gene deletion can extend the replicative lifespan in a CR pathway-dependent manner. These findings demonstrate that the repression of enhanced gluconeogenesis effectively extends the cellular lifespan.